In Search of The Holy Grail: How to Achieve Pro-Poor Growth? - Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2003)
Pro Poor Growth has become a central concern to achieve sustainable poverty reduction in developing countries. Despite being widely used, the term is not well-defined nor has there been a clear policy document that would summarize the determinants and policy implications of pro poor growth. This paper seeks to fill this void by first proposing a definition of pro poor growth, then summarizing the linkages between inequality, poverty, and pro poor growth, before proceeding to analyze the micro and sectoral determinants of pro poor growth. The final section spells out the recently emerging consensus on policy implications for pro poor growth, with particular emphasis on policy issues in Sub Saharan Africa and points to remaining disagreements and areas for further research. The paper emphasizes the particular importance of inequalityreducing policies for pro poor growth as well as the need to further analyze the scope of activist state policies to deliver a pro poor agenda.
Keywords: E6; I3; O1; 330; Pro Poor Growth; Inequality; Sub Saharan Africa; Sectoral and regional policies; Wachstumspolitik; Armutspolitik; Einkommensverteilung; Entwicklung; Entwicklungspolitik; Entwicklungsländer